2022
DOI: 10.1186/s12936-022-04047-3
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening therapeutic adherence and pharmacovigilance to antimalarial treatment in Manaus, Brazil: a multicomponent strategy using mHealth

Abstract: Background Public health initiatives for improving adherence to primaquine based regimens and enhancing effective pharmacovigilance are needed to support the efforts for malaria elimination in real world conditions. Methods A multicomponent patient-oriented strategy using a Smart Safety Surveillance (3S) approach including: (1) educational materials for treatment counselling and identification of warning symptoms of haemolytic anaemia; (2) an mHeal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…When considering the studies that do specify the psychiatric adverse effects, the most common symptom is depressive mood, 14,17,21,22,27,40 followed by anxiety symptoms 7,21,22,40 and hallucination. 27,39,40 In less frequency, studies also mentioned that patients developed psychosis, 7,17,21 agitation, 7,40 disturbed/strange thoughts, 7,14 depressive psychosis, 7 manic psychosis, 7 restlessness, 7 irritable mood, 7 panic attack, 17 confusion, 16 post-traumatic stress disorder (PTSD), 22 delirium, 27 and emotional lability. 39…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When considering the studies that do specify the psychiatric adverse effects, the most common symptom is depressive mood, 14,17,21,22,27,40 followed by anxiety symptoms 7,21,22,40 and hallucination. 27,39,40 In less frequency, studies also mentioned that patients developed psychosis, 7,17,21 agitation, 7,40 disturbed/strange thoughts, 7,14 depressive psychosis, 7 manic psychosis, 7 restlessness, 7 irritable mood, 7 panic attack, 17 confusion, 16 post-traumatic stress disorder (PTSD), 22 delirium, 27 and emotional lability. 39…”
Section: Resultsmentioning
confidence: 99%
“…Among those studies that do specify the length of treatment, individuals took CQ for a mean of 6 days, ranging from 6 hours to 18 days. 7,11,16,19,20,39,40,80 Using a different approach, Petersen et al 14 classified individuals into short-term (ie, less than 8 weeks of treatment) and long-term (ie, more than 8 weeks). The authors found, however, no significant difference in the percentage of psychiatric adverse effects between them.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies about patient adherence to antimalarials yielded varied results related to patient characteristics, the nature of their consultation with the provider, and methodological variations of the study [12]. Assessment of adherence relied on subjective measures such as self-reporting or a combination of selfreporting and more objective measures such as pill count, presenting empty pill bags, or directly measuring the level of PQ in the blood [13][14][15][16]. Treatment supervision to improve adherence has been studied, including in the trial where this study is embedded [17,18].…”
Section: Introductionmentioning
confidence: 99%